Faktor Risiko Penyakit Ginjal Kronik Stadium Terminal Pada Penderita Hipertensi Stadium 1-2 - Kartika Ikawati; Shofa Chasani (Universitas Pekalongan, 2017)
Background : End Stage Renal Disease (ESRD) has been a health problem because the incidence to increase with high mortality. Risk faktors of ESRD of stage 1-2 hypertention in during 5-10 years have not been studied. Risk faktors of ESRD ware associated with behaviors and comorbidity diseases in hypertension patientsMethod : This study applied an analytical observational method with a case control study design. The study used 64 respondents as sampels , divided into; 32 as case samples and 32 as control samples with consecutive sampling. Independent variabels in this study ware behavior, history of diabetes mellitus, hyper total cholesterol and hyper uric acid. Data were collected by interview and medical record. These data were subject to analyses using univariat, bivariate, and multivariate testsResults : Risk faktors of ESRD of stage 1-2 hypertention in during 5-10 as followings: type-2 diabetes mellitus (OR=39 ; 95% CI=5.435-73.531; P=0.000), not regularly taking anti-hypertensive drugs (OR=14; 95%CI=2.117-92.170; P=0.006) and hyper total cholesterol (OR=13; 95% CI=2.136-81.025; P=0.005). .Conclusion : Risk factors for ESRD in hypertension patients were; type-2 diabetes mellitus, not regularly taking anti-hypertensive drugs and hyper total cholesterol. To prevent the progression of hypertension into ESRD, strived not to suffered type 2 diabetes mellitus, taking anti-hypertensive medication regulary and control of total cholesterol Keywords : Risk Faktors, End Stage Renal Disease, Hypertension